2016
DOI: 10.1111/iwj.12603
|View full text |Cite
|
Sign up to set email alerts
|

Health economic burden that different wound types impose on the UK's National Health Service

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
271
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(283 citation statements)
references
References 9 publications
8
271
0
4
Order By: Relevance
“…Briefly, several authors reported that differences in the HRs are explained by the vast heterogeneity in the baselines due to the inclusion of ulcers with different sizes and of different duration [18, 19]. Our results confirm the above reports and show that the inclusion of ulcers of different sizes (large and short) and ulcers of different durations (short and long) contribute to severe heterogeneity in the baselines and differences in the HR among the reviewed bandages of four-LB, SSB compression, two-L SSB, four-L LSB, two-L LSB, and KTwo [12, 24, 27-30, 32, 34, 35, 42-44]. Again, this heterogeneity is still a significant limitation in the design of the current research, which needs to be addressed in future clinical studies.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Briefly, several authors reported that differences in the HRs are explained by the vast heterogeneity in the baselines due to the inclusion of ulcers with different sizes and of different duration [18, 19]. Our results confirm the above reports and show that the inclusion of ulcers of different sizes (large and short) and ulcers of different durations (short and long) contribute to severe heterogeneity in the baselines and differences in the HR among the reviewed bandages of four-LB, SSB compression, two-L SSB, four-L LSB, two-L LSB, and KTwo [12, 24, 27-30, 32, 34, 35, 42-44]. Again, this heterogeneity is still a significant limitation in the design of the current research, which needs to be addressed in future clinical studies.…”
Section: Discussionsupporting
confidence: 87%
“…However, the cost for treatment varies in different countries. For example, in the United Kingdom, the estimated annual cost of VLU treatment is GBP 941.1 million to treat approximately 300,000 patients [12]. In Australia, the annual cost of VLU treatment is estimated to be USD 784.66 million to treat 47,299 cases.…”
Section: Introductionmentioning
confidence: 99%
“…This concurs with Guest et al (2016) who described confusion and confliction with wound treatment plans when the dressing types were switched at successive wound dressing changes. In this study, those living with PI are in contact with health professionals for extended periods of time where health-related quality of life living with a PI was influenced by opportunities for dialogue and mutual decision making between patients and health professionals, with agreement about symptoms and treatment plans allowing patients to regain some control and independence (Gorecki et al, 2009).…”
Section: Discussionsupporting
confidence: 85%
“…Yet, care provided in the home setting is a vital component of PI prevention and management, and is a growing component of health care systems. Guest et al (2016) calculated that two-thirds of UK wound care expenditure is incurred in the community setting, with PI patients requiring 1.6 million community nurse visits annually, costing in excess of £88 million. A significant number of patients developed PI whilst in community-based care (Moore & Cowman, 2012), and Worsley et al (2016) found 81% of patients (n=1026) admitted to hospital with a community-acquired PI came from their own homes, rather than formal care settings.…”
Section: Introductionmentioning
confidence: 99%
“…The natural history is that of a continuous cycle of healing and breakdown of skin tissues over decades, causing considerable disability and impaired quality of life1. It has been estimated that the UK National Health Service (NHS) manages 278 000 venous leg ulcers each year, at an annual cost of €1024 million (£941 million; exchange rate £1 = €1·0882), mostly in primary care and community nursing services3. Moreover, with an ageing and increasingly overweight population, the prevalence of venous ulceration is likely to increase.…”
Section: Introductionmentioning
confidence: 99%